Prove that the sum of the squares of the first n integer is 1/24 (2n) (2n+1) (2n+2).?

6 Answers

Relevance
  • seah
    Lv 7
    1 decade ago
    Best answer

    Let say

    1^2 + 2^2 + 3^2 + ... + n^2 = 1/24 (2n) (2n+1) (2n+2)

    is true for n

    for n+1,

    1^2 + 2^2 + 3^2 + ... + n^2 + (n+1)^2

    = 1/24 (2n) (2n+1) (2n+2) + (n+1)^2

    = 1/24 (2n) (2n+1) (2n+2) + 1/24 (24)(n+1)^2

    = 1/24 [(2n) (2n+1) (2n+2) + 24(n+1)^2]

    = 1/24 [(2n)(4n^2+6n+2) + 24(n^2+2n+1)]

    = 1/24[8n^3 +12n^2 +4n + 24n^2 +48n + 24]

    = 1/24[8n^3 + 36n^2 +52n + 24]

    = 1/24 ((2n+2)(2n+3)(2n+4)

    = 1/24 (2(n+1)) (2(n+1)+1)(2(n+1)+2)

    Proved for n+1

    for n= 1

    RHS

    1/24 (2(1)) (2(1)+1) (2(1)+2)

    = 1/24 (2)(3)(4)

    = 1 = 1^2

    same as LHS

    So, use Inductiom method

    1^2 + 2^2 + 3^2 + ... + n^2 = 1/24 (2n) (2n+1) (2n+2)

    is true for n >=1

    Source(s): myseah
  • 1 decade ago

    Start from the identities:

    (k+1)^2 - k^2 = 2k + 1 ........(1)

    (k+1)^3 - k^3 = 3k^2 + 3k + 1 ..........(2)

    Then:

    (2) * 2 - (1) * 3 gives:

    2[ (k+1)^3 - k^3 ] - 3[ (k+1)^2 - k^2 ]

    = 6k^2 - 1 .........(3)

    Note that when summing the left hand side from k = 1 to k = n, all terms in each of the square brackets disappear, except for the first term when k = n and the last term when n = 1.

    If s is the sum you require, then summing (3)

    from k = 1 to k = n gives:

    6s - 1

    = 2[ (n + 1)^3 - 1 ] - 3[ (n + 1)^2 - 1 ]

    = 2(n + 1)^3 - 3(n +1)^2 + 1

    6s = 2(n + 1)^3 - 3(n +1)^2 + 2

    = 2n^3 + 6n^2 + 6n + 2 - 3n^2 - 6n + 1

    = 2n^3 + 3n^2 + 1

    = n(2n + 1)(n + 1)

    Multiplying by 4 to obtain the rather unusual form you have:

    24s = (2n)(2n + 1)(2n + 2)

    s = (1/24)(2n)(2n + 1)(2n + 2).

  • 3 years ago

    start up from the identities: (ok+a million)^2 - ok^2 = 2k + a million ........(a million) (ok+a million)^3 - ok^3 = 3k^2 + 3k + a million ..........(2) Then: (2) * 2 - (a million) * 3 provides: 2[ (ok+a million)^3 - ok^3 ] - 3[ (ok+a million)^2 - ok^2 ] = 6k^2 - a million .........(3) be conscious that when summing the left hand facet from ok = a million to ok = n, all words in all the sq. brackets disappear, apart from the 1st time era whilst ok = n and the final time era whilst n = a million. If s is the sum you require, then summing (3) from ok = a million to ok = n provides: 6s - a million = 2[ (n + a million)^3 - a million ] - 3[ (n + a million)^2 - a million ] = 2(n + a million)^3 - 3(n +a million)^2 + a million 6s = 2(n + a million)^3 - 3(n +a million)^2 + 2 = 2n^3 + 6n^2 + 6n + 2 - 3n^2 - 6n + a million = 2n^3 + 3n^2 + a million = n(2n + a million)(n + a million) Multiplying via 4 to acquire the truly unusual style you have: 24s = (2n)(2n + a million)(2n + 2) s = (a million/24)(2n)(2n + a million)(2n + 2).

  • 1 decade ago

    First of all,

    2n ( 2n + 1) ( 2n + 2) / 24 = n ( n + 1) ( 2n + 1) / 6 .

    We want to prove :

    Σ i² = 1² + 2² + 3² + . . . + n² = n ( n + 1) ( 2n + 1) / 6 .

    If true for n = r , then adding ( r + 1)² to both sides

    1² + 2² + 3² + . . . + r² + ( r + 1)² = ( r + 1) ( r + 2) ( r + 3) / 6 .

    Substituting r + 1 for n shows that n + 1 is true,

    and since 1² = 1 ( 1+ 1) ( 2 + 1) / 6 is true,

    then every case for n is true.

  • What do you think of the answers? You can sign in to give your opinion on the answer.
  • smci
    Lv 7
    1 decade ago

    To prove: Σi² = (n)(2n+1)(n+1)/6

    Generally you either prove it by induction.

    (I was thinking you could prove it directly by squaring the more basic result of the sum of the first n integers:

    Σi = (n)(n+1)/2 = 1 +2 + ... + n

    but apparently you can't)

    Inductive proof:

    Assume Σi²_i=1_(n-1) = (n-1)(2n-1)(n)/6

    Then Σi²_i=1_n = Σi²_i=1_(n-1) + n²

    = (n-1)(2n-1)(n)/6 + n²

    = [ (n-1)(2n-1)(n) + 6n² ]/6

    = [ (n-1)(2n-1) + 6n ] * n/6

    = [ 2n²-3n+1 + 6n ] * n/6

    = [ 2n²+3n+1 ] * n/6

    = (n+1)(2n+1)n/6

    QED.

  • 1 decade ago

    Let me present something very general, never let people get away with induction as if they derived it,

    consider,

    f(n) = n^r .(n+1)^r - n^r .(n-1)^r -----(1)

    f(1) + f(2) +...+f(n) = n^r .(n+1)^r

    and the binomial theorem gives,

    f(n) /2 = rC1.n^(2r-1) + rC3.n^(2r-3)+....

    putting (n-1),(n-2),...,2,1 in succession for n and adding we have,

    n^r.(n+1)^r /2 = rC1 S(2r-1) + rC3 S(2r-3) +...

    where S(2r -k) is a sum of odd powers of integers.

    substitute a suitable r and get S1,S2,etc.

    Now find a similar relation for sums of even powers of integers, all you have to do is change a negative sign in (1)

Still have questions? Get answers by asking now.